Troubleshooting on Scale-Up Process of Microalgae Growth from Flask to Photobioreactor - Nur Adiba, Mohd Noor (2012)
Cultivation of microalgae in the photobioreactor at the optimum growth needs many considerations to be put in. The growth of microalgae will be based on CO2 supply, temperature and mixing. Another consideration is about the lighting supply. Thus, photobioreactor is designed based on the best criteria to produce the optimum growth. Based on the best criteria, scale-up process is done. To be successful in the scale-up process has many challenges and difficulties. Some of challenges with the growth of microalgae for oil production are that only a very thin layer of suspended algae in a few centimeters deep, is actually active in photosynthesis and. The objective of the research is to do the troubleshooting on scale-up process by using tubular photobioreactor. In this experiment, the microalgae used is Nannochloropsis sp. There are two parts of microalgae cultivation which are in lab scale (2L) flask and in 390L tubular photobioreactor. The reconstituted medium using sea salt and F/2 are prepared. Four runs with different condition in inoculum volume and sparging air flow rate have been done. Because of the unsuccessful scale-up run, two monitor experiments has been done in flasks based on insufficient inoculum volume and addition of carbon dioxide as causes of failure. From the monitor experiment on insufficient inoculum volume, it can be concluded that the failure of scale-up process is because of inoculum volume which is too dilute; 2.5%, 3.5%, 5% and also 10%. To ensure the scale-up process is successful, the inoculum volume need to be increased as well as denser the concentration of microalgae. In the monitor experiment on the addition of carbon dioxide, with the supplying of carbon dioxide at low flow rate, the growth of microalgae is increased day by day. It is proved that the addition of carbon dioxide at low flow rate is not the cause of failure of the scale-up process. Other causes of failure maybe because of the lower level in sparging air flow rate and photoperiod cycle. As a conclusion, the objectives is achieved and the troubleshooting process is done.